Lessons learned from a search for common ground. (February 2021) - Hess, Rick; Noguera, Pedro
In 2020, Rick Hess and Pedro Noguera engaged in a long-running correspondence that tackled many of the biggest questions in education — including topics like school choice, equity and diversity, testing, privatization, the achievement gap, social and emotional learning, and civics. They sought to unpack their disagreements, better understand one another's perspectives, and seek places of agreement or points of common understanding. Their correspondence appears in their book, A Search for Common Ground: Conversations About the Toughest Questions in K-12 Education (Teachers College Press, 2021). In this article, they reflect on the exercise, what they learned from it, and what lessons it might offer to educators, education leaders, researchers, and policy makers .